Addition of Soluble Fiber in Low-Fat Purified Diets Maintains Cecal and Colonic Morphology, Modulates Bacterial Populations and Predicted Functions, and Improves Glucose Tolerance Compared with Traditional AIN Diets in Male Mice. Issue 10 (16th June 2022) - Griffin, Laura E; Radhakrishnan, Sridhar; Pellizzon, Michael A
ABSTRACT: Background: Purified diets (PDs) contain refined ingredients with one main nutrient, allowing for greater control relative to grain-based diets (GBDs), which contain unrefined grains and animal byproducts. Traditional PDs like the American Institute of Nutrition (AIN)-76A (76A) and AIN-93G (93G) can negatively impact metabolic and gut health when fed long term, in part due to lower total fiber, no soluble fiber, and higher sucrose content. Objective: Two studies were conducted to determine how PDs with reduced sucrose and increased fiber (soluble and insoluble) influence metabolic and gut health in mice compared with traditional AIN PDs or GBDs. Methods: In study 1, C57Bl/6N mice ( n = 75) consumed a GBD [LabDiet 5002 (5002)], 76A, 93G, or 2 PDs with reduced sucrose and higher fiber for 88 d. Body composition and metabolic parameters were assessed. In study 2, C57Bl/6N mice ( n = 54) consumed either 2 GBDs (LabDiet 5001 or 5002) or PDs with different types/levels of fiber for 14 d. Microbiome alterations and predicted functional metagenomic changes were measured. Results: The PD with 75 g cellulose and 25 g inulin per 4084 kcals marginally influenced body weight and adiposity, but improved glucose tolerance relative to 93G ( P = 0.0131) and 76A ( P = 0.0014). Cecal and colonic weights were lower in mice fed cellulose-based PDs compared with those fed GBDs and soluble-fiber PDs. Soluble-fiber PDs reduced alpha diversity and showed similar beta diversity, which differed from cellulose-based PDs and GBDs. Certain genera associated with improved gut health such as Bifidobacteria and Akkermansia were significantly elevated by soluble-fiber PDs ( P ≤ 0.01). Metabolic pathways related to carbohydrate and fatty acid metabolism were affected by PDs. Conclusions: PDs formulated with lower sucrose and increased fiber content, particularly soluble fiber, blunted elevations in metabolic parameters and favorably impacted the microbiota and metagenome in C57BL/6N mice. Abstract : This work provides support for adding soluble fiber inulin in purified control diets such as the traditional AIN diets to maintain gut and metabolic health in male C57BL/6 mice.